On OPr. 119.13 ʃubban Aʃman (and OLith. patį aʃchmą) as a collective number - Dini, Pietro U. (Vilnius University Open Series, 2022)
The aim of this paper is to discuss the OPr. construction ʃubban Aʃman (cf. German selb acht, OLith. patį aʃchmą) attested in the liturgical supplement of the Baptism Booklet of Martin Luther’s Enchiridion (1561). The two terms are mostly traditionally considered as not related to one another. A new interpretation of this construction is given in this paper, based on a newly accomplished comparative and philological analysis of the passage involved. It is possible to say that we are dealing with a collective numeral, which was known also in Middle Europe-linguistic-context (examples from Middle Latin, Middle German, and West-Slavic are given). During the process of translation both an iconic imitation of the model and a servile calque played a major role for the emergence of OPr. ʃubban Aʃman (and OLith. patį aʃchmą). Despite the traditional interpretations, my conclusion is that the two terms are related indeed.
Keywords: Old Prussian; Old Lithuanian; Middle Europe-linguistic-context; collective numeral; translation process